A tale of woe and misgivings - Sunday, (2004)
I think I've finally had enough! I've had a bad cough from the time we were at the Kuala Kubu Baru (KKB) camp which only got worst after i got up to Universiti Putra Malaysia (UPM), most probably because I had to run in the rain twice despite having gone to the doctors twice in KKB and once in UPM.